Estudo sobre as exportações dos estados do Nordeste - Andrade, Maria Elza de (2015)
This dissertation main goal is to develop a study on the exports determinants for nine Northeast Brazilian States. In order to achieve this goal the dissertation includes three chapters and the analysis relies on the period of 1999 to 2012. The first chapter uses a set of economic and social indicators to construct a diagnostic for the Northeast States and develops a correlation analysis between the growth rates of exports and GDP and the export value and per capita GDP. The second one develops a set of data that allow one to have an overview of the export behavior for the States of the Northeast region during the investigation period. The third chapter estimates two vector autoregressive (VAR) models in order to understand the role played by the real effective exchange rate, the trade weighted foreign income based on the major ten export partners and the international commodity prices on exports for each one of the Northeast States. The empirical results suggests that the States of the Northeast Region have experienced significant economic and social advances during the period of analysis, but with few exceptions, these advances are still below the national indicators. Based on this preliminary analysis one can say that exports can be a channel to foster economic growth and development for the state economies. Exports have a significant growth, regardless of the decrease during 2009 for eight out of nine Northeast States. The export composition relies mainly on agriculture and mineral commodities, and manufactured products with low aggregate value and it is clear that there has been an increase in the number of new export partners. The empirical results (VAR) provides evidence that exports relies mainly on its own dynamics, however once commodity prices are included in the model there is some significant role for this variable. The real effective exchange rate and the trade weighted foreign income do not seem to have a significant role in explaining State exports.